Determination of Organochlorine Pesticides in Green Leafy Vegetable Samples via Fe3O4 Magnetic Nanoparticles Modified QuEChERS Integrated to Dispersive Liquid-Liquid Microextraction Coupled with Gas Chromatography-Mass Spectrometry - Ling Yu; Guiquan Guo; Jun Zhao; Linnan Zhao; Aiqing Xia; Xu He; Cuijuan Xing; Lili Dong; Fang Wang (Journal of Analytical Methods in Chemistry)
A fast method based on Fe3O4 magnetic nanoparticles (Fe3O4 MNPs) modified QuEChERS integrated to dispersive liquid-liquid microextraction (DLLME) coupled with gas chromatography-mass spectrometry was established for the determination of 8 organochlorine pesticides (OCPs) in green leafy vegetables. The factors involved in the purification by QuEChERS and concentration by DLLME were optimized. In the QuEChERS process, Fe3O4 MNPs were used as a new impurity adsorbent after the sample extraction procedure by acetonitrile, which achieved phase separation rapidly. Carbon black was used as an alternative to costly graphitized carbon black without affecting the recovery. In the process of DLLME, 1 mL of the extract obtained by QuEChERS was used as the dispersive solvent, 40 μL of chloroform was used as the extractive solvent, and 4 mL of water was added. Making them mix well, then the dispersed liquid-liquid microextraction concentration was subsequently carried out. The enrichment factors of 8 OCPs ranged from 22.8 to 36.6. The recoveries of the proposed method ranged from 78.6% to 107.7%, and the relative standard deviations were not more than 7.5%. The limits of detection and limits of quantification were 0.15–0.32 μg/kg and 0.45–0.96 μg/kg, respectively. The method has been successfully applied to the determination of OCPs in green leafy vegetable samples.